Recognizing ecosystem service's contribution to SDGs: Ecological foundation of sustainable development - Zihan Xu; Jian Peng (Geography and Sustainability)
There is less than half the time left to achieve the United Nations Sustainable Development Goals (SDGs), and progress toward SDGs is obviously insufficient. The contribution of ecosystem services (ES) to SDGs realization has received extensive attentions, but systematic generalization and recognition are still lacking. Based on a review of the progress and challenge of sustainable development, this study summarized ES’s potential contribution to 17 SDGs, and systematically reviewed empirical researches focused on the ES’s contribution to SDGs based on the RepOrting standards for Systematic Evidence Syntheses (ROSES). The results showed that from the 1960s to the 2020s, the ES’s contribution has gradually become more important in sustainable development. ES has potential contribution to all SDGs, but the contribution to different SDGs varies. In the empirical study, ES’s contribution to SDG2, SDG6, SDG13, and SDG15 were strongly focused. ES’s contribution to SDG4, SDG5, SDG10, SDG16, and SDG17 were weakly focused. Most researches have explored the ES’s contribution to SDGs based on ES supply at a single scale, lacking attentions to ES demand and scale differences, and insufficient attentions to intervention factors affecting the ES’s contribution to SDGs. Faced with the above deficiencies, future research could deepen the exploration of ES’s contribution to SDGs from the following four perspectives: clarifying true contributions, exploring leverage point, integrating multi-scale differences, and focusing on intervention factors.